Improvement of dynamical and tribological properties of friction systems by introducing parallel-grooved structures in elastic damping components. (15th May 2018) - Lu, X.D.; Zhao, J.; Mo, J.L.; Zhang, Q.; Zhang, X.; Zhou, Z.R.
Abstract: This paper presents the influence of introducing elastic damping components having different parallel-grooved structures in friction systems. Experimental and numerical studies are conducted to evaluate the effects on the friction-induced vibration, and friction and wear. A number of parallel-grooves structures are designed and manufactured on damping components. The experiments are performed using a purpose-built experimental test bench. The effects of different damping components on the dynamical and tribological properties are estimated by comparing the dynamic vibration performance, and friction and wear characteristics of the contact interface. The experimental results show that the system with damping components could effectively suppress the friction-induced vibrations, and improve the wear characteristics. Consequently, this helps stabilize system, especially for the damping components having the structure of two parallel grooves. The contact stress distribution of pad surface and the deformations of different damping components are evaluated through numerical studies. The observations and explanations are supported by experimental results.